Richard Nixon : California's Native Son - Carter, Paul (Paul Jeffrey) (Book collections on Project MUSE., 2023)
""Richard Nixon : California's Native Son" is Nixon's uniquely Southern California journey, his life in full circle from his birth in Yorba Linda, California, to his final resting place just a few yards from the home in which he was born"--